1999
DOI: 10.1046/j.1365-2052.1999.00434.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of milk protein allele frequencies in Nordic cattle breeds

Abstract: Allele frequencies at four milk protein loci were studied in five modern and 17 old Nordic cattle breeds in order to reveal variants that are characteristic for these populations. The B allele of CSN3, which has been associated with improved manufacturing properties of milk, showed significantly lower frequencies in modern production breeds than in old breeds of interest for conservation purposes. Characteristic frequencies of CSN1S1 (C), CSN2 (A2) and CSN3 (B) were found in Icelandic cattle, Swedish Mountain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
45
4
8

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 28 publications
9
45
4
8
Order By: Relevance
“…A predominance of α s1 -Cn B (or its monomorphism) has also been observed in the common dairy breeds in Europe (Tervala et al 1983, Ikonen et al 1996, Lundén et al 1997, Erhard et al 1998, Lien et al 1999. The same predominant variants in κ-and β-Cn loci have been found in most dairy cattle: κ-Cn A, except for Finncattle, Jersey and Brown Swiss, where B-allele is widespread, and alleles A 1 and A 2 at β-Cn (Tervala et al 1983, Ikonen et al1996, Freyer et al 1999.…”
Section: Discussionmentioning
confidence: 99%
“…A predominance of α s1 -Cn B (or its monomorphism) has also been observed in the common dairy breeds in Europe (Tervala et al 1983, Ikonen et al 1996, Lundén et al 1997, Erhard et al 1998, Lien et al 1999. The same predominant variants in κ-and β-Cn loci have been found in most dairy cattle: κ-Cn A, except for Finncattle, Jersey and Brown Swiss, where B-allele is widespread, and alleles A 1 and A 2 at β-Cn (Tervala et al 1983, Ikonen et al1996, Freyer et al 1999.…”
Section: Discussionmentioning
confidence: 99%
“…Frequencies of CSN1S1*B are in tendency higher and significantly higher for CSN1S1*b in northern than in southern European breeds, with highest values in dairy breeds of north western European origin. LIEN et al (1999) reported an apparently contrary frequency gradient in Nordic breeds with high frequencies of CSN1S1*C in autochtone breeds of northern Scandinavia and lower frequencies to fixation in dairy breeds originated in southern Scandinavia. This indicates rather a selection gradient than a geographic gradient, supporting the suggestion made by LIN et al (1986) that occurrence of CSN1S1*B variant is correlated with selection for improvement in milk production traits.…”
Section: Correlations and Regression Analyses With Geographic Datamentioning
confidence: 99%
“…It has been postulated that CSN1S1*B has positive effects on milk yield (LIN et al, 1986), whereas higher milk protein content is found in animal heterozygous for CSN1S1*BC compared to BB homozygous animals (NG- KWAI-HANG et al, 1990;ALEANDRI et al, 1990, BOVENHUIS et al, 1992. In Nordic cattle breeds LIEN et al (1999) identified an allele frequency gradient with low frequency of CSN1S1*B in native breeds to high frequency of CSN1S1*B and loss of CSN1S1*C in high selected dairy cattle. This is in agreement with the reported very high frequencies of CSN1S1*B in breeds selected for milk production, up to fixation or nearly-fixation in Ayrshire, Angler, or Holstein Friesian (ERHARDT, 1993;IKONEN et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…This has not been studied. The reason for less association between the incidence of type 1 diabetes and the sum of A1 and B ␤ -casein than with A1 alone in the present study might be the relatively large variation in the available fi gures for B ␤ -casein and that it is only found in measurable amounts in some breeds of cattle [7] . Another recent ecological study including 20 countries found per capita consumption of A1 ␤ -casein to be related to type 1 diabetes but did not fi nd B ␤ -casein to be signifi cantly correlated to the disease [15] .…”
Section: Discussionmentioning
confidence: 50%
“…Norway, Denmark, Sweden and Finland, which might explain the lower incidence of type 1 diabetes (per 100,000/year, 0-14 years) in Iceland [1,[7][8][9][10][11] . Furthermore, the increase in incidence in the youngest age group 0-4 years of age seen in the Nordic countries is not seen in Iceland.…”
Section: Introductionmentioning
confidence: 99%